Zinc removal from highly acidic and sulfate-rich wastewater in horizontal sub-surface constructed wetland - Shweta Singh; Saswati Chakraborty (Water Science and Technology, 2021)
This study demonstrated the successful use of a laboratory-scale baffled horizontal constructed wetland substituted with mixed organic media for zinc removal from high acidity (∼610 mg L−1 as CaCO3), sulfate-rich (∼1,300 mg L−1) wastewater. The wetland was planted with Typha latifolia. The mean zinc concentration in the influent was gradually increased from 0.56 ± 0.02 mg L−1 to 5.3 ± 0.42 mg L−1. The mean zinc concentration in the outflow was 0.22 ± 0.19 mg L−1, which accounted for 95% zinc removal throughout the study. However, total zinc uptake by the plants was 533 mg kg−1, accounting for only 1.2% of total zinc removal; therefore, major zinc retention occurred within wetland media (83%). The overall activity and specific sulfidogenic activity decreased at the end of the study to 1.43 mg chemical oxygen demand removed per mg of TVS per day and 0.60 mg sulfate reduced per mg of TVS per day, respectively. Additionally, 16S rRNA sequencing revealed major dominant phyla present: Firmicutes (36%), Proteobacteria (16%), Actinobacteria (8.8%), Planctomycetes (7.8%), Chloroflexi (3.5%), Acidobacteria (1.9%) and Fibrobacteres (1.5%). HIGHLIGHTS Effective acidity removal with alkalinity generation (35–750 mg L−1 as CaCO3).; CW exhibited good zinc removal efficiency (92–95%), with >80% retention in media.; Zinc uptake by plants was 533 mg kg−1, accounting for only 1.2% of total zinc removal.; Specific sulfidogenic activity accounted for 0.60–0.83 mg sulfate reduced per mg of TVS per day.; Metagenomics revealed the dominance of Firmicutes (36%) and Proteobacteria (16%).;